2022
DOI: 10.1029/2021ea001962
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Calibration of the Swiss Plate Geophone Bedload Monitoring System by Filtering Out Seismic Signals From Extraneous Particle Impacts

Abstract: The spatio‐temporal variability of bedload transport processes poses considerable challenges for bedload monitoring systems. One such system, the Swiss plate geophone (SPG), has been calibrated in several gravel‐bed streams using direct sampling techniques. The linear calibration coefficients linking the signal recorded by the SPG system to the transported bedload can vary between different monitoring stations by about a factor of six, for reasons that remain unclear. Recent controlled flume experiments allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…Recent findings by Nicollier, Antoniazza, Rieckenmann, et al. (2022) showed that it is possible to filter the spurious vibrations generated by impacts on nearby plates and on the concrete sill surrounding the plates array checking the spectral characteristics of impacts. Particles directly impacting the plate always presented a first part of the impact with high frequencies (larger than 1 kHz), whereas spurious impacts caused the plate to vibrate predominantly with a frequency in the range of the fundamental mode.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent findings by Nicollier, Antoniazza, Rieckenmann, et al. (2022) showed that it is possible to filter the spurious vibrations generated by impacts on nearby plates and on the concrete sill surrounding the plates array checking the spectral characteristics of impacts. Particles directly impacting the plate always presented a first part of the impact with high frequencies (larger than 1 kHz), whereas spurious impacts caused the plate to vibrate predominantly with a frequency in the range of the fundamental mode.…”
Section: Discussionmentioning
confidence: 99%
“…(2016c), Nicollier, Antoniazza, Rieckenmann, et al. (2022), and Nicollier, Antoniazza, Ammann, et al. (2022) developed a procedure to estimate grain size from the spectral centroid frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the two bedload transport monitoring systems may have different capabilities in terms of minimal grain‐size detection, which may translate into differences in bedload transport estimates. The SPG system has a detection threshold for particles greater than ∼10–20 mm (Nicollier et al., 2021; Nicollier, Antoniazza, Ammann, et al., 2022; Nicollier, Antoniazza, Rickenmann, et al., 2022; Wyss et al., 2016a, 2016b, 2016c), while seismic inversion may detect smaller particles if hydraulic and transport conditions allow it.…”
Section: Methodsmentioning
confidence: 99%
“…Antoniazza et al. (2020, 2022) and (Nicollier, Antoniazza, Ammann, et al., 2022; Nicollier, Antoniazza, Rickenmann, et al., 2022) describe the system and its calibration in detail. In this contribution, we used data from the monitoring station (a) to set the investigated bedload transport event into comparative context with other events that took place over the period 2016–2020 and (b) as a benchmark method to evaluate the seismic inversion approach for bedload transport sensing.…”
Section: Methodsmentioning
confidence: 99%